Discovering how lower grade university students spend their free time with media: The generation y scenario / Azniza Ahmad Zaini, Nor Aziah Abd Kadir and Mohd Zahid Laton - Ahmad Zaini, Azniza; Abd Kadir, Nor Aziah; Laton, Mohd Zahid (Universiti Teknologi MARA Cawangan Pahang, 2012)
This study was conducted to discover how lower grade students of Generation Y at one higher education institution in the East Coast Malaysia spend their free time with media. It is crucial for educators and parents to understand the role of media in young people’s lives as media is among the most powerful forces in the young people’s lives today. Media is also able to influence the activities that Generation Y students are engaged in during their free time because they are born in the digital age. The respondents for the study were lower grade students from a public university in Malaysia. Self-administered questionnaires were distributed to the respondents and the sample was obtained using a non-probability sampling technique. The data were analyzed using descriptive statistics. The results from this study are hoped to provide educators and parents with valuable information on the impact of media on youths, specifically the lower grade students at higher education institution.